2021Seguimiento del desempeño del rol profesional de los egresados de la Facultad de Odontología Universidad Antonio Nariño Sede Ibagué en los municipios del Espinal, Honda, Planada y Chaparral – Tolima, 2020. - Yanquel Urrego, Karol Alexandra; Conde Torres, Luisa Fernanda; Alfonso Sandoval, Karen Lizeth; Delgado Barrios, Stnefi; Gualtero Rojas, Stephanie (Universidad Antonio Nariño, 2021)
This project is aimed at monitoring graduates of the Ibagué Faculty of Dentistryheadquarters between the years 2001-2020-II, taking into account aspects of statistical traceability to show the impact they have had in the labor and social sphere. At the same time, it will be a tool that shows the integration of graduates with their alma mater. Raising the role of the graduate, their contribution and experience acquired in their work and professional life.